Dikotomi dan Simbiosis Metode Kualitatif serta Kuantitatif dalam Karya Tulis Ilmiah - Nurlena, Elin; Hayadi, B.Herawan; Zikriyanto, Wahyu; Oktalia, Huda; Hisaanah, Khauranina; Haryati, Reti Sri (STAI Darul Qalam Tangerang, 2026)
Methodological debates in the academic sphere are often ensnared in a rigid dichotomy between the positivism paradigm underlying quantitative methods and the interpretivism governing qualitative methods. This polarization creates epistemological barriers that frequently hinder researchers from capturing the wholeness and complexity of a phenomenon holistically. In fact, both paradigms possess significant symbiotic potential to strengthen the validity, reliability, and credibility of scientific findings through methodological convergence. This article aims to deeply map the roots of the differences (dichotomy) from philosophical to technical dimensions, while simultaneously exploring integration opportunities (symbiosis) between the two. By applying a literature study method on various contemporary methodological journals and fundamental literature, the study results indicate that although the dichotomy fundamentally lies in the foundations of ontology, epistemology, and axiology of data, symbiosis can be effectively achieved through triangulation strategies and mixed-methods designs. The study concludes that the integration of both methods is not merely a technical merger of instruments, but rather a manifestation of an epistemological approach capable of providing a more comprehensive understanding, rich in descriptive nuances, yet remaining empirically measurable. The recommendations of this article emphasize the importance of methodological flexibility for researchers in facing increasingly complex social and scientific phenomena in the contemporary era.